Exploring the value of organizational support, engagement, and psychological wellbeing in the volunteer context - Dekel, Grace; Geldenhuys, Madelyn; Harris, Jemma (Frontiers in Psychology, 2022)
Volunteer engagement may act as an important tool in supporting psychological wellbeing. In Australia, young adults are more likely to experience psychological distress than other age groups. The present study relies on the Job Demands Resources model and Self Determination Theory to help understand the negative consequences of high work demands, and the importance of effective organisational support to enhance positive mental health outcomes. To address research gaps, the current study explores these concepts for the young adulthood cohort in not-for-profit organisations. The study aims to explore the relationship between psychological wellbeing, volunteer engagement, and perceived organisational support. The study used a quantitative, cross-lagged, longitudinal method collecting data across a period of four weeks. Inclusion criteria of participants were volunteers that worked a minimum of four hours a month (on average), resided in Australia, and were between 19 – 40 years old (N = 202). They completed two online surveys four weeks apart. The main study findings were that perceived organisational support mediated the relationship between psychological wellbeing at time point one and volunteer engagement at time point two. However, perceived organisational support did not mediate volunteer engagement at time point one and psychological wellbeing at time point two. There were no bidirectional effects between volunteer engagement and psychological wellbeing. The findings contributed to the existing literature suggesting there are overlaps between support mechanisms and motivation between paid and unpaid work. The practical implications for not-for-profit organisations are the importance of providing organisational support for young adult volunteers to improve wellbeing outcomes. Limitations and future study recommendations are presented.